Health coaching interventions for persons with chronic conditions: a systematic review and meta-analysis protocol. Issue 1 (December 2016) - Boehmer, Kasey; Barakat, Suzette; Ahn, Sangwoo; Prokop, Larry; Erwin, Patricia; Murad, M.
Abstract Background Chronic conditions are increasingly more common and negatively impact quality of life, disability, morbidity, and mortality. Health coaching has emerged as a possible intervention to help individuals with chronic conditions adopt health supportive behaviors that improve both quality of life and health outcomes. Methods/design We planned a systematic review and meta-analysis of the contemporary health coaching literature published in the last decade to evaluate the effect of health coaching on clinically important, disease-specific, functional, and behavioral outcomes. We will include randomized controlled trials or quasi-experimental studies that compared health coaching to alternative interventions or usual care. To enable adoption of effective interventions, we aim to explore how the effect of intervention is modified by the intervention components, delivering personnel (i.e., health professionals vs trained lay or peer persons), dose, frequency, and setting. Analysis of intervention outcomes will be reported and classified using an existing theoretical framework, the Theory of Patient Capacity, to identify the areas of patients' capacity to access and use healthcare and enact self-care where coaching may be an effective intervention. Discussion This systematic review and meta-analysis will identify and synthesize evidence to inform the practice of health coaching by providing evidence on components and characteristics of the intervention essential for success in individuals with chronic health conditions. Systematic review registration PROSPEROCRD42016039730